Pectoralis Plane Block for Pacemaker Insertion: A Successful Primary Anesthetic - Mavarez, Ana C.; Ripat, Caroline I.; Suarez, Maria R. (Frontiers in Surgery, 2019)
Effective anesthesia, analgesia, and hemodynamic stability is important to maintain during pacemaker implantation surgery, especially in the elderly population and patients with compromised cardiac function. As a strategy to avoid the need for intravenous (IV) anesthetics, peripheral nerve block techniques may be used in these specific cases. We report a case of successful pacemaker implantation surgery in a patient with severe Aortic Stenosis (AS) and Sick Sinus Syndrome (SSS) using unilateral pectoralis plane block for surgical anesthesia. Since general anesthesia was considered risky, monitored anesthesia care utilizing peripheral nerve block was planned. A single shot left side pectoralis plane block (PECS II) was done under ultrasound guidance injecting a total of 20 mL of 0.5% Ropivacaine with 1% Lidocaine. No sedation was needed. The patient tolerated the procedure with no significant hemodynamic changes. Patient did not require opioids post-operative and was discharged home in stable condition the next day. This case highlights that PECS block can also provide effective surgical anesthesia for relatively long procedures avoiding the risk of complications associated with IV anesthesia in high risk cardiovascular patients. Additionally, these blocks can provide an opioid sparing option for post-operative management in pacemaker implantation surgeries.